Children with autism spectrum disorder: Pilot studies examining the salivary microbiome and implications for gut metabolism and social behavior. (March 2020) - Forsyth, Anna; Raslan, Kareem; Lyashenko, Claudia; Bona, Samantha; Snow, Michael; Khor, Brandon; Herrman, Elisa; Ortiz, Stephanie; Choi, Dongseok; Maier, Tom; Machida, Curtis A.
Abstract: Introduction: Autism Spectrum Disorder (ASD) is a collection of neurodevelopmental disorders defined by core deficits, including impaired communication, reciprocal social interaction, and stereotyped and repetitive patterns of behaviors. The salivary microbiota may serve as important indicators of oral and systemic health. In this pilot study, we identify components of the salivary microbiome in children with ASD. Methods: Saliva specimens were collected from 11 children with ASD (mean age: 10.68 years) and from 10 typically-developing individuals. Microbial DNA was extracted and utilized as templates for PCR amplification with V3-V4 16S rDNA-specific primers and high-throughput MiSeq sequencing. Taxonomic operational unit analyses and salivary microbiota profiles were conducted by LC Sciences (Houston TX); individual microbial species were further compared between children with ASD and typically-developing individuals. Results: Rothia species were found to be statistically more prevalent in children with ASD in comparison to typically-developing children (12.2-fold change; FDR p-value = 0.031). Alternately, Megasphaera, Moraxella, Neisseria, and Gemella species were all found at significantly higher levels in typically-developing children than children with ASD, displaying 39.2-, 31.9-, 18.8- and 14.0-fold differences, respectively (all with FDR p-values < 0.011). In boys with ASD, Moraxella and Neisseria species were found at significantly-higher levels compared to typically-developing counterparts, exhibiting 42.36- and 28.62-fold differences, respectively (FDR p-values of 0.011 and 0.0004). Conclusion: Understanding the salivary microbiome in children with autism can lead to improved management of oral health and precision treatment planning. In addition, practitioners may be able to modify the oral microbiome as therapeutic regimens for ASD and other oral diseases.